Thermal, magnetic and spectral studies of metal-quinone complexes Part III. radical coordination and hydrogen bonding mediated exchange interaction in copper-hydroxyquinone complex - Salunke-Gawali, S.; Rane, S. Y.; Boukheddaden, K.; Codjovi, E.; Linares, J.; Varret, F.; Bakare, P. P. (Journal of Thermal Analysis and Calorimetry, 2005)
The reaction of CuCl with 2HNQ, ( viz. 2- hydroxy- 1,4- naphthoquinone), in methanol results in [Cu-2( II, II)(4HNSQ)(2)(ONQ)(2)(H2O)(4)], Cu- 3 complex; [ where ONQ is the deprotonated oxidized form of ligand ( viz. 2- oxido- 1,4- naphthoquinone) and 4HNSQ one electron reduced tautomeric form of the ligand (i.e. 4- hydroxy - 1,2- naphthosemiquinone)]. The mixed valent redox ligation is confirmed in [ 9] by us. In present report complex Cu- 3 investigated by variable temperature magnetic susceptibility measurements ( SQUID), X and Q- band EPR, DSC and CV techniques. A break is observed in the chi(m)(-1) vs. T plot similar to 200 K in Cu- 3 which is attributed to a phase transition. In Cu- 3 a quintet state ( S= 2) is populated above 200 K by the molecular association of two exo Cu( II)( 4HNSQ) units via hydrogen bonding between Cu(ONQ) unit of endo ligands in dimer. Magnetic susceptibility data is treated with tetramer model with S= 1/2,1/2,1/2,1/2. The interdimer triplet- triplet interaction ( J) in two [ Cu( 4HNSQ)] units and intradimer ( zJ(1)) interaction between [ Cu( II)( 4HNSQ)] are best fitted with J= -50 cm(-1) and zJ(1)= 28 cm(-1), respectively, using g= 2.2. `Quintet- triplet' phase transition occurs with an enthalpy change of 31.83 kJ mol(-1) estimated from DSC. Cu( II)double left right arrow Cu( I) and NSQ double left right arrow CAT redox couples at E-1/2= 0.68 V and E-1/2 = -1.12 V, respectively are result of exo ligands and Cu( II) ions interaction, while shifts of ligand based peaks viz. NQ -> NSQ and NSQ double left right arrow CAT at - 0.44 and - 0.67 V towards positive potential on complexation are due to electron transfer interactions between endo ligand and Cu( II) ion.
Keywords: antiferromagnetic coupling; copper complexes; Lawsone; model complexes; quinones; triplet state

Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Reaction between lawsone and aminophenol derivatives: synthesis, characterization, molecular structures and antiproliferative activity - Kathawate, Laxmi; Joshi, Pranya V.; Dash, Tapan Kumar; Pal, Sanjima; Nikalje, Milind; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Reaction between two bioreductive reactants lawsone (2-hydroxy-1,4-napthoquinone) and derivatives 2-aminophenol without catalyst is reported. The reaction between lawsone and 4-chloro-2-aminophenol leads to formation of red colored major product 1A:[2-[(5-chloro-hydroxyphenyl)amino]naphthalene-1,4-dione] and fluorescent orange colored minor compound 1B:[10-chloro-benzo[alpha]phenoxazine-5-one]. Molecular structure of 1A and 1B were determined by single crystal X-ray diffraction. Two mechanisms were proposed to the formation of red 1A and 1B. `Ortho-para' tautomeric equilibrium was observed in DMSO-d(6) solution in 1A, which was revealed by H-1, C-13 NMR and LC-MS studies. Molecules of 1A formed dimers via N-H center dot center dot center dot O interaction and polymeric chain of dimers was formed by OH center dot center dot center dot O interactions. Cl center dot center dot center dot Cl interactions were observed between the polymeric chains of dimers in 1A. Molecules of 1B show Cl center dot center dot center dot N interaction. Antiproliferative properties is studied for 1A-5A compounds (obtained by the reaction of lawsone with 2-amino-4-methylpheno1;2A, 2-aminopheno1;3A, 3-aminophenol;4A and 4-aminophenol;5A) and evaluated against two cancer cell lines, THP1 (human monocytic leukemia cells) and COLO205 (colorectal adenocarcinoma) and one normal cell line, HEK293T (human embryonic kidney). The values of 50% inhibitory concentration (IC50) of compounds 1A-5A was determined using XTT assay. The cytotoxic effects of compounds 2A and 3A were observed against COLO205 and compounds 4A and 5A on THP1 were observed to be higher in comparison to their effect on HEK293T cell lines. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Aminophenol; Benzo[alpha]phenoxazine; Cl center dot center dot center dot N interactions; Lawsone; pi-pi stacking interaction